Benefits of Canavalia ensiformis, arbuscular mycorrhizal fungi, and mineral fertilizer management in tobacco production - Ponce de Leon, Daniel; Garcia Rubido, Milagros; Rivera, Ramón; Mancero-Castillo, Daniel; Garcia, Yoansy (Frontiers in Agronomy, 2024)
Tobacco (Nicotiana tabacum L.) has long been vital to Cuban agriculture, with its products renowned for their quality. Cuban tobacco is grown in soils with a long history of continuous farming using traditional fertilization methods characterized by recommended doses of mineral fertilizers. This study aims to improve the nutrition resource strategy in tobacco cultivation to ensure high yields of superior-grade tobacco leaves with adequate quality and increase fertilization efficiency. With this goal, a field experiment evaluated the traditional method of fallow with alternatives of nutrient supply systems for the production of black tobacco in Ultic Paleustalf soils. The experiment utilized Canavalia ensiformis (Can) treated with a mycorrhizal inoculum (AMF) based on the Glomus cubense strain (INCAM-4) as a preceding green manure, combined with successive mineral fertilizations for tobacco during four growing seasons in a randomized block design with factorial arrangement. Canavalia presented a positive response to mycorrhizal inoculation, significantly increasing dry biomass production (87.34%, 129.96%), mycorrhizal colonization (26.90%, 103.66%), and spore production (26.79%, 52.52%) for Can and Can+AMF treatments respectively. A biplot analysis established a strong relationship between the biomass and mycorrhizal performance of Canavalia and the growth, yield, and mycorrhizal colonization of tobacco. The results indicate that inoculated Canavalia enhances mycorrhizal performance in successional tobacco, with Can+AMF significantly increasing mycorrhization of tobacco roots by (110.06%). Moreover, the combination of Can inoculate with AMF and 75% of the recommended mineral fertilization dose consistently produced the highest tobacco yields (42.06%), growth, and mycorrhizal activity across the four years while maintaining satisfactory combustibility. In this nutrition supply system, variations of the recommended fertilizer dose significantly decreased the percentage of mycorrhizal colonization. After four growing seasons using Can + AMF and Canavalia without inoculations, soil organic matter, and availability of exchangeable calcium, magnesium, and pH increased slightly without decreasing available phosphorus and potassium contents. Consequently, we conclude that Canavalia ensiformis, with an inoculum based on the Glomus cubense strain and 75% of the recommended dose of mineral fertilizers, provides an enhanced nutrition alternative system for black tobacco production.